Alejandro Cesarco, Nancy Davenport, Renée Green, Annette Lawrence, Scott Lyall, Dave McKenzie, Bettina Pousttchi, Haim Steinbach on On Kawara - Cesarco, Alejandro 1975-; Davenport, Nancy 1965-; Green, Renée 1959-; Lawrence, Annette ca. 20./21.Jh; Lyall, Scott 1964-; McKenzie, Dave 1977-; Pousttchi, Bettina 1971-; Steinbach, Haim 1944- (Dia Art Foundation, 2021)
This is the sixth volume in a series that builds upon Dia Art Foundation's Artists on Artists lectures. The contributors to this book explore the practice of On Kawara (1932-2014) from various points of entry: Alejandro Cesarco uses a self-reflexive approach to the ideas of artistic legacy, influence and work; Nancy Davenport contends with innocence and trauma in two of Kawara's most influential series; Renée Green weaves a poetic relationship between the work of Chantal Akerman and Kawara; Annette Lawrence provides a close reading of the Today series and her own journals, grappling with what it means to keep time; Scott Lyall considers the experience and contingency of time, differentiating between thinking with and speaking about a work of art; Dave McKenzie stages a diaristic correspondence with Kawara; Bettina Pousttchi reflects on duration in art and the history of time keeping; and Haim Steinbach plays with Beckettian abstraction, absurdity and repetition
Keywords: Kawara, On -- 1933-2014